2016
DOI: 10.1049/iet-map.2015.0179
|View full text |Cite
|
Sign up to set email alerts
|

Rectangular microstrip antenna with dumbbell shaped defected ground structure for improved cross polarised radiation in wide elevation angle and its theoretical analysis

Abstract: A simple and compact rectangular microstrip patch antenna (RMPA) with dumbbell shaped defected ground structure has been proposed and investigated experimentally for significant suppression of cross polarised (XP) radiation compared with maximum co‐polarised gain without affecting the co‐polarised radiation pattern. The investigation shows that the proposed antenna has an excellent co‐polarised radiation to XP radiation isolation over wide elevation angle around the broadside for different aspect ratio (width … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(18 citation statements)
references
References 26 publications
(30 reference statements)
1
17
0
Order By: Relevance
“…Consequently it may affect the radiation property of RMA. Some recent investigations clearly demonstrate that the electric fields corresponding to the next higher order orthogonal mode TM 02 , which in fact, is situated near nonradiating edges of the patch is the major factor which contributes in XP radiation. The electric field component corresponding to TM 02 mode beneath the patch as obtained from is Ex=Ccos2πWz …”
Section: Theoretical Analysis and Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently it may affect the radiation property of RMA. Some recent investigations clearly demonstrate that the electric fields corresponding to the next higher order orthogonal mode TM 02 , which in fact, is situated near nonradiating edges of the patch is the major factor which contributes in XP radiation. The electric field component corresponding to TM 02 mode beneath the patch as obtained from is Ex=Ccos2πWz …”
Section: Theoretical Analysis and Designmentioning
confidence: 99%
“…A clear physical insight in to the observed improvement in XP radiation may also be extorted out from the distribution of electric field magnitude over the patch surface, which is depicted in Figure . The thorough literatures establish that, the main sources of XP are the radiation from nonradiating edges and patch corners of a RMA. Therefore, to reduce the radiation from nonradiating edges, we need to minimize the field magnitude there.…”
Section: Theoretical Analysis and Designmentioning
confidence: 99%
“…It increases with the size of dot-type defect and consequently reduces the Q factor, which in turn, enhances the impedance bandwidth. Moreover, the fields of orthogonal component of dominant mode that lies near the patch corners also contribute to XP radiation as is evident from [11,14,15]. 2.…”
Section: I T H E O R E T I C a L B A C K G R O U N D A N D P A R mentioning
confidence: 99%
“…Around 16% impedance band width with more than 25 dB of CP-XP isolation is revealed in [14] for RMA. One very recent report [15] shows the theoretical analysis of rectangular-headed dumbbell DGS-integrated RMA, where around 25 dB of CP-XP isolation is achieved for all width to length ratios (0.8 to 1.6) of a patch.…”
Section: Introductionmentioning
confidence: 99%
“…The asymmetry of the probe location results in asymmetry in the near fields in the vicinity of the antenna, causing high XP radiation in the Hplane of the antenna. XP reduction using symmetric arcshaped DGS [7], asymmetric DGS [8], a strategic design of DGS [9], and a dumbbell shaped DGS, without affecting co-polarized radiation pattern [10] have been explored to understand the effectiveness of DGSs towards this issue. It has been found that the XP reduction along with proper impedance matching is a difficult task for the MSA designers.…”
Section: Introductionmentioning
confidence: 99%